Crospovidone-wrapped single walled carbon nanotubes solubility: solute-solvent interaction & structural mechanism / Malahah Mohamed - Mohamed, Malahah (2015)
Crospovidone is a highly hydrophobic polymer but has a good capability as a carrier and excipient. With the aid of surfactant (SDS), the solubilization of single walled carbon nanotubes (SWNTs) in water has been achieved by polymer wrapping. Polymer wrapped single walled carbon nanotubes (SWNTs) have been synthesized to improve the solubility of SWNTs in water. The synthesized crospovidone wrapped single walled carbon nanotubes (CPVP-SWNTs) have been characterized using the solid state characterization tools such as Fourier transformation infrared spectroscopy (FTIR), Differential scanning calorimeter (DSC), X-ray diffractometer (XRD) and Field emission scanning electron microscope (FESEM) to ascertain the procedure of polymer wrapping. As there has been no literature on the solute-solvent interaction of the wrapped nanoparticles in water, the present study deals with the solute-solvent interaction and thermodynamic parameters during the solubilization of CPVP-SWNTs in water by viscometric, conductometric, volumetric and ultrasonic velocity methods. Viscosity, density and conductometry values of both CPVP and CPVP-SWNTs have been determined in water with different concentrations (0.05-1.2 gm/1) at temperatures 298.15, 303.15, 308.15 and 313.15K. The viscosity values have been evaluated in terms of AF (Falken-Hagen coefficient), Bj (Jones-Dole coefficient), dB/dt, A^ 0 (contribution per mole of the solute to free energy of activation for viscous flow of solutions), A^i° (corresponding value for pure solvent) and r)oAo (Walden product). Meanwhile, the conductance values have been used to evaluate the limiting molar conductance (Ao) and the activation energy (Es). From the density values, the limiting partial molar volumes and expansibilities have been calculated. However, ultrasonic velocity values of both CPVP and CPVP-SWNTs have been determined in water maintaining different concentration (0.05-1.2 gm/1) at only one temperature 298.15 K. Values of sound velocity have been used to evaluate the parameters such as isentropic compressibility (Ks), apparent isentropic molar compressibility (K°s), internal pressure (nt), relative association (Ra), acoustic impedance (Z) and free volume (Vj). It is observed that sound velocity increased with the increase in solute concentration with an almost linear fashion. The compressibility values are observed to decrease with increase in solute concentration and the estimated parameters were discussed in terms of solute-solvent interactions.